Trigger Video of Simulated Intraoperative Cardiac Arrest - Sara Goldhaber-Fiebert; Kyle Harrison; Sesh Mudumbai; Steven K. Howard; Kam McCowan; David M. Gaba (Association of American Medical Colleges, 2010)
Abstract Introduction At Stanford University School of Medicine and the Veterans Affairs Palo Alto Healthcare System, anesthesia residents felt they were missing an understanding of, and the ability to practice, the principles of crisis resource management (CRM) during an intraoperative crisis. Given residents extensive training using a high-fidelity patient simulator, and appreciation for the ability to both make mistakes without hurting patients, we created this intraoperative cardiac arrest simulation. This resource is a first step in bridging the gap between the theoretical and active application of team management principles by trainees. Methods The session for both resident and instructor training begins with a trigger video for interactive discussion. The video is not presented as a perfect model, but rather as a practical example of how principles of CRM may be applied in situ. Participants are encouraged to discuss how specific principles were applied effectively or not and how this affects patient care. Participates then proceed to several simulated scenarios during which they can practice, reflect on, and discuss how they themselves apply the principles of CRM. Results The use of this trigger video in our CRM simulation course, has been positively received by all participants. One trainee stated: "It was extremely helpful to see a model of how to actually put into action the principles of CRM. In watching and discussing the video, I became better equipped to implement the principles myself in subsequent simulations and in actual patient care." Discussion It is important to give medical trainees a controlled environment in which to practice CRM and reflect on their medical/teamwork management of the scenario. This trigger video and simulation are a favorable tool for creating a controlled environment.